Visual Style in the “Golden Age” Anthology Drama: The Case of CBS - Horwitz, Jonah (Cinémas, 2013)
Despite the centrality of a “Golden Age” of live anthology drama to most histories of American television, the aesthetics of this format are widely misunderstood. The anthology drama has been assumed by scholars to be consonant with a critical discourse that valued realism, intimacy and an unremarkable, self-effacing, functional style—or perhaps even an “anti-style.” A close analysis of non-canonical episodes of anthology drama, however, reveals a distinctive style based on long takes, mobile framing and staging in depth. One variation of this style, associated with the CBS network, flaunted a virtuosic use of ensemble staging, moving camera and attention-grabbing pictorial effects. The author examines several episodes in detail, demonstrating how the techniques associated with the CBS style can serve expressive and decorative functions. The sources of this style include the technological limitations of live-television production, networks’ broader aesthetic goals, the seminal producer Worthington Miner and contemporaneous American cinematic styles.